TINJAUAN YURIDIS TERHADAP PENGGUNAAN PLAT NOMOR KENDARAAN BERMOTOR YANG DIMODIFIKASI DI INDONESIA - Ridhotul Hairi; Dessy Artina; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The modification process indeed produces its own satisfaction for the owner, but it is very unfortunate because the results of these modifications often do not pay attention to legal norms and rules so that these modifications result in violating existing laws. An example is the use of modified motor vehicle license plates. In Indonesia the crime of violating the modification of motor vehicle license plates has not been clearly regulated in the laws and regulations. But it is only regulated, namely for every person who is not fitted with a license plate or motorized vehicle number that is official or determined by the police regulated in Article 280 of Law Number 22 Year 2009 concerning Road Traffic and Transportation.The research method in this study. First, the type of research is normative law and descriptive analysis. Second, data sources are supported by primary data sources, secondary data, and tertiary data. Third, the data collection technique used is literature review. After the collected data is then analyzed qualitatively and draw conclusions with deductive thinking method that is analyzing the problem from a general form to a special form.From the results of the problem research, there are two main things that can be concluded, First, the regulation of sanctions on the use of modified motor vehicle license plates based on Indonesian positive law refers to criminal penalties. Law Number 22 Year 2009 concerning Road Traffic and Transportation. Second, the imposition of sanctions is ideal to be applied to motorists who use modified motor vehicle license plates in Indonesia. The imposition of sanctions on violators of criminal offenses must be given special sanctions that can make deterrent such as imprisonment sanctions or fines.Based on this, Indonesia should make further rules regarding criminal offenses to modify motorized vehicle number plates into a form of legislation such as laws on traffic and road transport and weighting penalties by giving appropriate sanctions to the offenses.